BENDA MUATAN ASAL KAPAL TENGGELAM SITUS KARANG KIJANG BELITUNG: SURVEI AWAL ARKEOLOGI BAWAH AIR - Sofian, Harry Octavianus (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2011)
Belitung island surrounded by two straits, the Gaspar Strait and the Strait Karimata known by sailors as a strait which has many reefs and shoals of sand that can cause the ship sank. Belitung island known as the underwater archaeological sites in the form of ships sank. One of the places is Karang Kijang Site, this paper will discuss the archaeological preliminary survey conducted in this sites, which is expected to increase data Indonesia underwater archeological sites.